American Pharoah [large type] : the untold story of the Triple Crown winner's legendary rise - Drape, Joe (Thorndike Press large print biographies and memoirs., 2016)
History was made at the 2015 Belmont Stakes when American Pharoah won the Triple Crown, the first since Affirmed in 1978. Award- winning New York Times sportswriter Joe Drape offers the definitive account not only of how the ethereal colt won, but how he changed lives.